The gothic machinery in The Lord of the Rings - Scotuzzi, Nathalia Sorgon (Revista de Letras, 2017)
This paper intends to analyze elements of the gothic machinery inside the fantasy work The Lord of The Rings. A chronological analyses will be made, regarding concrete (such as monsters and locations) and subjective (the atmosphere and sensations experienced by the characters) elements related to the gothic and terror, and which function they fulfill in this work. The goal is to evidence how fundamental these elements are to the construction of the narrative, shaped as challenges to be overcome.